2007
DOI: 10.1002/yea.1501
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol‐mediated inhibition of Candida albicans yeast growth and rescue by a diacylglycerol analogue

Abstract: During Candida albicans yeast cell growth to early stationary phase, metabolites accumulate in the medium, including the quorum-sensing molecule farnesol. We found that besides germ tube inhibition, 40 µM farnesol also inhibited C. albicans yeast growth under yeast growth permissive conditions. Consistent with this observation, transcriptional analysis of yeast cells resuspended in fresh medium with 40 µM farnesol revealed that genes involved in hyphal formation, GTPase activation, mitosis and DNA replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 58 publications
8
41
0
1
Order By: Relevance
“…This repression was also observed in C. dubliniensis and C. parapsilosis (Jabra-Rizk et al, 2006;Rossignol et al, 2007). Interestingly, a cell cycle mechanism was only monitored for C. albicans (Uppuluri et al, 2007). The present study demonstrated that the effect of E ,E -farnesol is also influenced by the temperature and nutrient conditions (Table 4, Figure 4).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This repression was also observed in C. dubliniensis and C. parapsilosis (Jabra-Rizk et al, 2006;Rossignol et al, 2007). Interestingly, a cell cycle mechanism was only monitored for C. albicans (Uppuluri et al, 2007). The present study demonstrated that the effect of E ,E -farnesol is also influenced by the temperature and nutrient conditions (Table 4, Figure 4).…”
Section: Discussionsupporting
confidence: 68%
“…Their growth was significantly influenced by its addition. Several publications have reported in vitro growth inhibition by E ,E -farnesol (Davis-Hanna et al, 2008;Shirtliff et al, 2009;Uppuluri et al, 2007). This repression was also observed in C. dubliniensis and C. parapsilosis (Jabra-Rizk et al, 2006;Rossignol et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…albicans e A. nidulans (Voziyan et al, 1995;Yang e Kazanietz, 2003;Taylor et al, 2005;Fairn et al, 2007;Uppuluri et al, 2007;Savoldi et al, 2008;Román et al, 2009). A expressão constitutiva de Pkc1 leva a resistência de S. cerevisiae frente à presença de farnesol, possivelmente pela atividade na regulação da produção de espécies reativas de oxigênio (EROs) na cadeia de transporte de elétrons da mitocôndria (Fairn et al, 2007).…”
Section: -Peptídeo Sinal E Via Secretóriaunclassified